2016
DOI: 10.1007/s10562-016-1792-8
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4@RGO@Au@C Composite with Magnetic Core and Au Enwrapped in Double-Shelled Carbon: An Excellent Catalyst in the Reduction of Nitroarenes and Suzuki–Miyaura Cross-Coupling

Abstract: Magnetic core double-shelled carbon with Fe 3 O 4 nanoparticles as the core, reduced graphene oxide (RGO) as the inner shell and carbon (C) layer as the outer shell, have been successfully designed and prepared. This tailor-making structure acts as an excellent capsule for encapsulating Au nanoparticles (Au NPs), which could effectively prevent Au NPs from aggregation and leaching. Because of its structural features, magnetic coredouble-shell Fe 3 O 4 @RGO@Au@C architecture exhibits extremely high catalytic pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…[292] Dabiri et al prepared Fe 3 O 4 @RGO@Au@C composites which demonstrated excellent catalytic performance for the reduction of nitrophenols and the Suzuki-Miyaura cross-coupling reaction. [293] Barberry fruit extract was employed as a reducing and stabilizing agent for the environmentally friendly in situ synthesis of Cu NPs supported on a RGO-Fe 3 O 4 nanocomposite. The final Cu/RGO-Fe 3 O 4 material displayed high catalytic activity for the O-arylation of phenols using aryl halides.…”
Section: Magnetically Separable Catalysismentioning
confidence: 99%
“…[292] Dabiri et al prepared Fe 3 O 4 @RGO@Au@C composites which demonstrated excellent catalytic performance for the reduction of nitrophenols and the Suzuki-Miyaura cross-coupling reaction. [293] Barberry fruit extract was employed as a reducing and stabilizing agent for the environmentally friendly in situ synthesis of Cu NPs supported on a RGO-Fe 3 O 4 nanocomposite. The final Cu/RGO-Fe 3 O 4 material displayed high catalytic activity for the O-arylation of phenols using aryl halides.…”
Section: Magnetically Separable Catalysismentioning
confidence: 99%
“…In 2016, Dabiri and co‐workers reported a novel magnetic core double‐shelled carbon with Fe 3 O 4 NPs as the core, reduced graphene oxide (RGO) as the inner shell and carbon (C) layer as the outer shell (Fe 3 O 4 @RGO@Au@C) (Figure ) . The Fe 3 O 4 @RGO@Au@C nanocatalyst was successfully applied in the reduction of nitroarenes and Suzuki‐Miyaura cross coupling reactions of aryl halides with phenylboronic acid (Scheme ).…”
Section: C−c and C−x Coupling Reactions Catalyzed By Graphene Supportmentioning
confidence: 99%
“…Recently, studies on 2D mesoporous materials/graphene nanocomposites, prepared using graphene as a template, have been reported. Here, the presence of graphene is expected to provide a highly effective conduction path, which would facilitate the application of mesoporous materials/graphene nanocomposites as electrodes in batteries, fuel cells, sensors, super capacitors, and catalysis …”
Section: Introductionmentioning
confidence: 99%